Postinfantile Giant Cell Hepatitis Secondary to Rheumatoid Arthritis. Issue 4 (19th April 2023) - Martinez-Moad, Miranda; Wunderlich, Grant; Diep, Darlene; Vasudevan, Akshay; Russell, Alison; Janitz, Tyler; Aluri, Bineetha; Oviedo, Angelica; Mysore Rangaraju, Ayyappa
ABSTRACT: Postinfantile giant cell hepatitis (PIGCH), also known as syncytial giant cell hepatitis, continues to be a poorly defined and rare disease presentation in the adult population. Although a common finding in neonates, there is limited literature on the disease process, causes, and treatment success of PIGCH in adults. A strong association between autoimmune disorders and PIGCH, considerably so in the case of autoimmune hepatitis, has been established. However, there have been limited to no reports of PIGCH secondary to rheumatoid arthritis. Our clinical case aims to bring forth a vignette of PIGCH to spotlight this ill-defined disease in the adult population and highlight some of the proposed causes, treatments, and laboratory markers.